سولا السيرة والاعمال العسكرية والسياسية - فهد القيسي, محمد; فوزي, رغدة (Journal of College of Education, 2021)
Sulla (Lucius Cornelius) (187-78 BC) Leaders and consuls Romans distinguished, as it was in the beginning of his military company of the Consul Marius in his military campaigns, has helped him to catch the King of New Media (Theograth) towards (104 BC)., Then the Sula by subjecting the Germanic tribes - and Teutonic Alkamira - year 102 BC. Sola has won resounding fame during the war with the King of the Kingdom of Pontes (Mtheradats VI) year 88 BC. M. The Sulla and evaluate historians man feat built his glory with his hand, as she was born in an impoverished, but it later became, and after leading a series of wars, as well as its political, which was characterized as a defender of class supervision, a person of a place known in the history of the Republic of Romania. And known for his literary and artistic taste, as he was fond of collecting masterpieces of art, and it was advisable Arts Greek and Romanian. Despite the concerns of literary and artistic, it was the most realistic, as was the hardest cruelty, and indicates the severity of excessive lists issued by after taking office in Rome, which allowed any person under which the killing of any person whose name appears in these lists without exposure to any accountability, So named to these lists (lists of Sula ) And the importance of this character in the history of the Republic of Romania, came to this research sheds light on them .